Voluntary work in Fragile communities - Einarsdóttir, Jónína; Rafnsdóttir, Guðbjörg Linda (Félagsfræðingafélag Íslands, 2023)
Rural Iceland is popular among foreign volunteers, who perform a variety of jobs in exchange for food and housing. Those who recruit volunteers are accused of breaching collective agreements and wage theft when volunteers work in economic activities or on farms. The article aims to answer the question: Promote voluntary work done by foreign or domestic volunteers, localities that participated in the project “Fragile Communities” or do they take jobs from people who would want to live there if there were job opportunities? Data was collected in four areas included in the project “Fragile Communities”. During the fall of 2022 and spring of 2023, about 30 people were interviewed, and advertisements for volunteers were analysed. The interviewees agreed on respecting the labour market rules, independent of whether the volunteers were domestic or foreign. The context of voluntary work was seen as necessary and acceptable to disrespect principles of collective agreements, competition, and professional knowledge if it would benefit society. The idea of foreign volunteers taking paid jobs from local people was rejected. The interviewees agreed that voluntary work is vital to rural areas and a prerequisite for the communities. Dreifbýli Íslands er vinsæll viðkomustaður erlendra sjálfboðaliða sem gegna fjölbreyttum störfum í stað fæðis og húsnæðis. Aðilar sem ráða til sín sjálfboðaliða eru sakaðir um brot á kjarasamningum og launaþjófnað, vinni sjálfboðaliðar í efnahgslegri starfsemi og á lögbýlum. Markmið greinarinnar er að svara spurningunni: Efla sjálfboðastörf, unnin af erlendum eða innlendum sjálfboðaliðum, byggðarlög sem tóku þátt í verkefninu Brothættar byggðir eða taka þau störf frá fólki sem vildi búa þar ef atvinnutækifæri væru fyrir hendi? Gagna var aflað í fjórum byggðum sem tóku þátt í verkefninu Brothættar byggðir. Haustið 2022 og vorið 2023 voru tekin viðtöl við um 30 einstaklinga. Jafnframt voru auglýsingar greindar, þar sem óskað er eftir sjálfboðaliðum. Viðmælendur sammæltust um þá meginreglu að virða ...